INTERFERENSI GRAMATIKAL BAHASA JAWA TERHADAP BAHASA INDONESIA PADA TULISAN SISWA SMAN 1 RASAU JAYA - Arwani, Khozin; Madeten, Sisilya Saman; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to describe the form and type of grammatical interference in Javanese language to Indonesian. There are 46 studentâ€™s writings that are subject to study. The method used in this research is descriptive method with a form of this study is qualitative, and using sociolinguistic approaches. Data is taken from the students writing at SMAN 1 Rasau Jaya. The results of analysis of this study was obtained 78 sentences containing grammatical interference. Grammatical interference is divided into 43 sentences containing morphology interference and 35 sentences containing syntactic interference. Morphology form of interference is divided into morpho-phonemic interference and morphological interference. Syntactic form of interference is divided into word formation interference, clause structure interference, task word interference, and sentence pattern interference.Keywords: sociolinguistics, morphology interference, syntactic interferenceÂ